2018
DOI: 10.1523/jneurosci.1808-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinally Mapping Childhood Socioeconomic Status Associations with Cortical and Subcortical Morphology

Abstract: Childhood socioeconomic status (SES) impacts cognitive development and mental health, but its association with human structural brain development is not yet well characterized. Here, we analyzed 1243 longitudinally acquired structural MRI scans from 623 youth (299 female/324 male) to investigate the relation between SES and cortical and subcortical morphology between ages 5 and 25 years. We found positive associations between SES and total volumes of the brain, cortical sheet, and four separate subcortical str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
159
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 154 publications
(192 citation statements)
references
References 55 publications
(41 reference statements)
24
159
4
Order By: Relevance
“…Consistent with previous findings (Hanson et al, , ; Leonard et al, ; Luby et al, ; McDermott et al, ; Noble et al, ), we observed indications of variations in hippocampal structure by IPR among males. However, unlike previous results, we observed that lower IPR males showed evidence of outward local shape variation in the right anterior hippocampus (CA1 region).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Consistent with previous findings (Hanson et al, , ; Leonard et al, ; Luby et al, ; McDermott et al, ; Noble et al, ), we observed indications of variations in hippocampal structure by IPR among males. However, unlike previous results, we observed that lower IPR males showed evidence of outward local shape variation in the right anterior hippocampus (CA1 region).…”
Section: Discussionsupporting
confidence: 93%
“…Supplemental analyses of volume found a similar pattern of a positive association between IPR and thalamic volume in males and a negative association in females, although only for females did the result survive stringent Bonferroni correction. Our finding in females supports McDermott et al () who found that lower SES was associated with lower thalamic volume and inward shape changes. The thalamus is a key center for integrating basal ganglia networks that underlie the ability to modulate behaviors, for example, the expression of goal directed behaviors through movement, and the processes of emotion, motivation, and cognition that lead to movement (Haber & Calzavara, ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, evaluation of the hippocampus performed to date has been restricted to whole volume measurement only. M. Chakravarty et al, 2015;McDermott et al, 2019;Schroeder et al, 2017). M. Chakravarty et al, 2015;McDermott et al, 2019;Schroeder et al, 2017).…”
Section: Introductionmentioning
confidence: 99%